Empiric Deworming and CD4 Count Recovery in HIV-Infected Ugandans Initiating Antiretroviral Therapy - Lankowski, Alexander J.; Tsai, Alexander C.; Kanyesigye, Michael; Bwana, Mwebesa; Haberer, Jessica E.; Wenger, Megan; Martin, Jeffrey N.; Bangsberg, David R.; Hunt, Peter W.; Siedner, Mark J. (PLOS Neglected Tropical Diseases, 2014)
Author Summary It is estimated that up to half of all people infected with HIV in sub-Saharan Africa are co-infected with one or more gastrointestinal parasites. These parasitic infections may negatively impact the ability of the immune system to combat the HIV virus, leading to worse clinical outcomes in people with HIV. Therefore, routine, universal, empiric treatment of gastrointestinal parasite infections (“deworming”) has been suggested as one strategy for optimizing HIV outcomes in this region. Previous studies have provided conflicting results on whether empiric deworming positively impacts markers of HIV disease progression such as CD4 count and viral load, but all of these studies were performed in HIV-infected individuals not yet on antiretroviral therapy. In this study, we measured the association between receipt of empiric deworming and CD4 count over time in HIV-infected adults taking antiretroviral therapy in southwestern Uganda, an area with a high parasite burden. We found that, overall, there was no significant association between deworming and change in CD4 count; however, when we performed a sub-analysis looking exclusively at females during the first year of ART, deworming was associated with significantly increased CD4 count. These results suggest that empiric deworming may not be an effective generalized strategy for improving HIV treatment outcomes in sub-Saharan Africa; however, the possibility of targeted benefit in specific sub-populations deserves further investigation.